N′-[(3-Methyl-2-thienyl)carbonyl]isonicotinohydrazide - Naveenkumar, H. S. (International Union of Crystallography, 2009)
In the title compound, C(12)H(11)N(3)O(2)S, the pyridine ring is inclined to the thiophene ring, forming a dihedral angle of 34.96 (7)°. The mean plane through the hydrazide unit forms dihedral angles of 21.57 (8) and 53.08 (8)°, respectively, with the pyridine and thiophene rings. The two O atoms are twisted away from each other, as indicated by the C—N—N—C torsion angle of −81.27 (15)°. In the crystal structure, molecules are linked into an extended three-dimensional network by intermolecular N—H⋯N, N—H⋯O and C—H⋯O hydrogen bonds. The crystal structure also features a short S⋯O [3.2686 (10) Å] interaction and a weak intermolecular C—H⋯π interaction.